2000
DOI: 10.1136/gut.47.2.236
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies against the specific epitope of human tropomyosin(s) detected by a peptide based enzyme immunoassay in sera of patients with ulcerative colitis show antibody dependent cell mediated cytotoxicity against HLA-DPw9 transfected L cells

Abstract: Background and aims-Recent studies suggest that tropomyosin (TM) may act as a putative autoantigen in ulcerative colitis (UC). Recently, we identified, by computer homology analysis, a specific peptide (HIAEDADRK) in human TM that can bind to HLA-DPw9. The aim of this study was to investigate the presence of autoantibodies against this peptide in UC. Conclusions-Anti-TM antibody was detected in UC sera by a specific peptide based ELISA with high reproducibility. This peptide may be an antigenic epitope of TM i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 30 publications
1
26
0
Order By: Relevance
“…Das et al 10 detected antibody reacting against porcine TM in UC sera. Recently, Sakamaki et al 7 reported that anti-TM antibody may be involved in the pathogenesis of UC. Anti-TM antibody in our patient became positive when UC became symptomatic, but disappeared with remission although we could not study other autoantibodies associated with UC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Das et al 10 detected antibody reacting against porcine TM in UC sera. Recently, Sakamaki et al 7 reported that anti-TM antibody may be involved in the pathogenesis of UC. Anti-TM antibody in our patient became positive when UC became symptomatic, but disappeared with remission although we could not study other autoantibodies associated with UC.…”
Section: Discussionmentioning
confidence: 99%
“…7 Antibody titers were represented by optical density (OD) values at 405 nm. The normal range was defined as 0.04 to 0.6, OD values from 40 healthy volunteers (mean Ϯ2 s.d.…”
Section: Case Reportmentioning
confidence: 99%
“…Antibodies against hTM5 have been detected in UC patients without PSC [28] , and antihTM5 in UC sera has recently been shown to induce cytotoxicity against colonic epithelial cells in vitro [29] . In PSC patients without concomitant UC, a single study identified antibodies against a 9-amino acid sequence from hTM (not isoform specific) in 100% (8/8) of patients as compared with 69% (33/48) of UC patients and 0/6 PBC patients [30] . The findings of Das et al have been partly reproduced by others [31] , but given a number of critical concerns [32][33][34][35] , further studies are required to conclusively confirm and elaborate the importance of the hTM5-CEP antigen in the pathogenesis of PSC.…”
Section: Antibodies Against Biliary and Colonic Epithelial Antigensmentioning
confidence: 99%
“…Perinuclear antineutrophil cytoplasmic antibody (pANCA) and antitropomyosin antibodies as well as autoantibodies against heat-shock proteins, epithelial cells, and goblet cells have been described. [21][22][23][24] Although pANCA is used to distinguish between IBD subsets, none of the mentioned antibodies show high sensitivity, and they have not yet been implicated in the pathogenesis of the disease.…”
mentioning
confidence: 99%